2013
DOI: 10.1155/2013/259680
|View full text |Cite
|
Sign up to set email alerts
|

Histology and Ultrastructure of Transitional Changes in Skin Morphology in the Juvenile and Adult Four‐Striped Mouse (Rhabdomys pumilio)

Abstract: The four-striped mouse has a grey to brown coloured coat with four characteristic dark stripes interspersed with three lighter stripes running along its back. The histological differences in the skin of the juvenile and adult mouse were investigated by Haematoxylin and Eosin and Masson Trichrome staining, while melanocytes in the skin were studied through melanin-specific Ferro-ferricyanide staining. The ultrastructure of the juvenile skin, hair follicles, and melanocytes was also explored. In both the juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For tightness of the junction between the dermis and the epidermis, the hemidesmosomes were found, while the desmosomes were presented in abundant numbers at the level of stratum basale to ensure the adhesion between the keratinocytes. The morphometric and histological studies of the skin have been broadly concentrated in a few mammalian animal groups including the four‐Striped Mouse (Stewart, Ajao, & Ihunwo, 2013), Brandt's hedgehog (Bazm et al, 2020), Pinnipeds (Khamas, Smodlaka, Leach‐Robinson, & Palmer, 2012), and Sphynx feline (Genovese, Johnson, Lamb, & Gram, 2014). The snout skin of the domestic pig ( Sus scrofa domesticus ) was composed of the epidermis and the dermis (cutis).…”
Section: Discussionmentioning
confidence: 99%
“…For tightness of the junction between the dermis and the epidermis, the hemidesmosomes were found, while the desmosomes were presented in abundant numbers at the level of stratum basale to ensure the adhesion between the keratinocytes. The morphometric and histological studies of the skin have been broadly concentrated in a few mammalian animal groups including the four‐Striped Mouse (Stewart, Ajao, & Ihunwo, 2013), Brandt's hedgehog (Bazm et al, 2020), Pinnipeds (Khamas, Smodlaka, Leach‐Robinson, & Palmer, 2012), and Sphynx feline (Genovese, Johnson, Lamb, & Gram, 2014). The snout skin of the domestic pig ( Sus scrofa domesticus ) was composed of the epidermis and the dermis (cutis).…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin wax tissue blocks were sectioned at 6 mm, and then hematoxylin and eosin (HE) staining was performed. The detail methods were described previously (Stewart, Ajao, & Ihunwo, 2013). To further distinguish the differences between the various groups, Lillie staining was also performed.…”
Section: Histological Analysismentioning
confidence: 99%
“…The integument connects the animal with the external environment and protects underlying organs from mechanical trauma and infection. Several studies have shown that the rodent integumentary properties are habitatspecific, and vary even for rodents of the same genus but diverse habitats (4)(5)(6). In the light of this, the present study aims to describe the gross and histologic structures of the trunk and paw pad skin of the African palm squirrel in relation to its habitat.…”
Section: Introductionmentioning
confidence: 96%